How high might the revenue-maximizing tax rate be? - Dan Usher (Queen's University, Department of Economics, 2014)
Through tax evasion, through the labour-leisure choice or in other ways, taxpayers reduce the tax base in response to an increase in the tax rate. The process is commonly-believed to generate a humped Laffer curve with a revenue-maximizing tax rate well short of 100%. That need not be so. In the "new tax responsiveness literature", the revenue-maximizing tax rate is inferred from the observed "elasticity of taxable income". It is shown in this article 1) that the inference is unwarranted because the elasticity of taxable income may vary with the tax rate, 2) that the "new tax responsiveness literature" imposes the implicit assumption that tax revenue falls to 0 when the tax rate rises to 100%, 3) that tax revenue may increase together with the tax rate all the way up to 100% and 4) that the Laffer curve is ill-defined because tax revenue at any given rate may depend upon how tax revenue is spent.
Keywords: H21; H23; 330; revenue-maximizing tax rate; Laffer curve